2018
DOI: 10.25081/jsa.2018.v2.884
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of phosphate fertilizer enriched with low molecular weight organic acids on phosphorus release kinetic and availability under calcareous conditions in arid region

Abstract: The objective of this work was to investigate the effect of some low-molecular-weight organic acids (LMWOAs) on phosphorus release and availability in calcareous soil. Experiments were conducted in laboratory. Soil-limestone mixtures were prepared to achieve highly calcareous samples (i.e. 50% CaCO3). The prepared samples were mixed thoroughly with phosphate fertilizers i.e. Triple super phosphate (TSP) and Mono-ammonium Phosphate (MAP) and watered with distilled water only (CK), with citric acid solution (CA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…At the present time, there is an urgent need to seek strategies by which P fertilizers can be used more effectively in soils rich in calcium carbonate of Algeria, thus, attempting to complement the previous knowledge on the optimization of phosphorus fertilization in the calcareous soil of Algeria (Mihoub et al, 2016;Mihoub et al, 2017;Mihoub et al, 2018). So, the objectives of this research were to investigate the beneficial effect of integrating P fertilizer with organics substances on combating P deficiency and reducing the reliance on phosphorus fertilizers for wheat cropped on alkaline-calcareous soils.…”
Section: Introductionmentioning
confidence: 99%
“…At the present time, there is an urgent need to seek strategies by which P fertilizers can be used more effectively in soils rich in calcium carbonate of Algeria, thus, attempting to complement the previous knowledge on the optimization of phosphorus fertilization in the calcareous soil of Algeria (Mihoub et al, 2016;Mihoub et al, 2017;Mihoub et al, 2018). So, the objectives of this research were to investigate the beneficial effect of integrating P fertilizer with organics substances on combating P deficiency and reducing the reliance on phosphorus fertilizers for wheat cropped on alkaline-calcareous soils.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the amount of soil available P in AWSB1 and AWSB2 amended treatments is higher compared to the control (without biochar input) and even compared with WSB treatments (Figure 2). This could probably be attributed to the acidification of soil/biochar by citric acid which can compete strongly with P for adsorption sites by blocking phosphate sorption sites on soil thereby reducing phosphate adsorption [14]. Organic acids have been reported to strongly enhance the mobilization of P from soils [15,16].…”
Section: Resultsmentioning
confidence: 99%
“…The low pH of the soil plays a vital role in the dissolution of immobilized soil P [17]. Addition of organic acids to the soil caused an immediate pH drop and the extent of pH decrease depended on both soil type and organic compound [18,14]. According to Hopkins et al [19], the decrease of soil pH (6.5) will increase the mobility of fixed soil P. In the case of low soil pH, the activity of H+ will decompose the bond of calcium and phosphorus in the calcareous soil.…”
Section: Resultsmentioning
confidence: 99%
“…This was clear with the insoluble sources RP and BS. The following descending order generally appeared in the chemically extractable mount of P with addition of solubilizing agents: citric acid > EDTA > HA > compost for these sources of P. Mihoub et al (2018) reported that after a period of 960 h from incubation of highly calcareous soil samples (50 % CaCO 3 ) fertilized with triple superphosphate and mono-ammonium phosphate and treated with citric acid and oxalic acid solutions, treatments showed a significant decrease in extractable P with time, however, applying these solutions exerted a very favorable effect on P solubility in soil. Also, in our study, with the addition of dissolving bacteria to the studied treatments activated the bacteria in dissolving the insoluble sources beside binding phosphate groups.…”
Section: Incubation Experimentsmentioning
confidence: 97%